2017
DOI: 10.19183/how.24.1.311
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Listening in a Colombian University: Process, Product, and Perceptions

Abstract: The current paper reports an experience implementing a small-scale narrow listening scheme (one of the varieties of extensive listening) with intermediate learners of English as a foreign language in a Colombian university. The paper presents (a) how the scheme was designed and implemented, including materials and procedures (the process); (b) how the students performed in the different activities with an emphasis on time spent watching/listening and their perceptions of video difficulty and self-rated compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 9 publications
1
33
0
1
Order By: Relevance
“…Based on the research result presented earlier, it is obvious that extensive listening provides positive influence on the students' listening skill. It is in line with the finding of some previous studies (Reinders&Cho, 2010;Onoda, 2012;Chang &Millett, 2013;Ducker, 2013;Hapsari&Ratri, 2013;Bozan, 2015;Mayora, 2017). With extensive listening activities, it was found that students' listening score increased quite significantly in Cycle 1 though it did not attain the criterion of success yet (55% students got ≥75 with the average score of 75.36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the research result presented earlier, it is obvious that extensive listening provides positive influence on the students' listening skill. It is in line with the finding of some previous studies (Reinders&Cho, 2010;Onoda, 2012;Chang &Millett, 2013;Ducker, 2013;Hapsari&Ratri, 2013;Bozan, 2015;Mayora, 2017). With extensive listening activities, it was found that students' listening score increased quite significantly in Cycle 1 though it did not attain the criterion of success yet (55% students got ≥75 with the average score of 75.36).…”
Section: Discussionsupporting
confidence: 91%
“…Not few research reports on extensive listening have been published, and mostly confirm the positive effect on the improvement of listening skill (Reinders&Cho, 2010;Onoda, 2012;Chang&Millett, 2013;Hapsari&Ratri, 2013;Mayora, 2017). Investigating Turkish college students, Bozan (2015) reports the significant role of extensive listening on the students' overall English skills, proficiency level and motivation for a more sustainable learning.…”
mentioning
confidence: 99%
“…Based on the findings of many researchers on the field, such as Kiany and Shiramiry [24], Mayora [20], that different listening activities have a positive effect on improving L2 listening fluency, we suggested the hypothesis that the experimental group practising EL would have a higher level of performance than the control group practising listening in traditional way.…”
Section: Research Questionsmentioning
confidence: 95%
“…Brown [16] conducted two small studies at a university in Japan to explore the benefits of this new extensive listening practice but he only focused on investigating the students" perceptions of EL. Recently, Mayora [20] reported the experience of employing a smallscale narrow listening scheme as one of the varieties of EL with intermediate English learners at a Colombian university. Unlike previous studies, our research project aims to initiate students" selecting and checking the difficulty level of listening practice materials by designing their own listening tests for other students in the experimental group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The widespread internet access nowadays, teachers are given more a variety of authentic learning resources using audiovisual materials such as video, TV programs, online learnings (Mayora, 2017). Teachers nowadays can get more accessible and downloadable listening materials to use in and outside the classroom.…”
Section: Introductionmentioning
confidence: 99%